2019
DOI: 10.1093/annweh/wxz056
|View full text |Cite
|
Sign up to set email alerts
|

Derivation of Time-Activity Data Using Wearable Cameras and Measures of Personal Inhalation Exposure among Workers at an Informal Electronic-Waste Recovery Site in Ghana

Abstract: Objectives Approximately 2 billion workers globally are employed in informal settings, which are characterized by substantial risk from hazardous exposures and varying job tasks and schedules. Existing methods for identifying occupational hazards must be adapted for unregulated and challenging work environments. We designed and applied a method for objectively deriving time-activity patterns from wearable camera data and matched images with continuous measurements of personal inhalation expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 32 publications
3
32
0
Order By: Relevance
“…Comprehensive description of PM determination can be found in [27]. Briefly, PM in the breathing zone of participants was measured using a MetOne Aerocet 831 particle mass profiler (MetOne Instruments Incorporated, Grants Pass, OR, USA) which simultaneously measured PM2.5 and PM10 levels per minute at a flow rate of 2.8 L/min.…”
Section: Particulate Matter Exposure Assessmentmentioning
confidence: 99%
“…Comprehensive description of PM determination can be found in [27]. Briefly, PM in the breathing zone of participants was measured using a MetOne Aerocet 831 particle mass profiler (MetOne Instruments Incorporated, Grants Pass, OR, USA) which simultaneously measured PM2.5 and PM10 levels per minute at a flow rate of 2.8 L/min.…”
Section: Particulate Matter Exposure Assessmentmentioning
confidence: 99%
“…The e-waste recyclers were usually present at the worksite from about 7 am to 6 pm. A detailed study of their time-activity budgets revealed that they worked 6 to 7 days per week at an average of 10 h per day [47]. Our instruments were calibrated to sample for 4 h, and usually between the period of 8 am and 2 pm.…”
Section: Measures Of Real-time Personal Pm 25 Levelsmentioning
confidence: 99%
“…In wave III, the sampling duration was reduced to approximately 2 h due to the high levels of PM from the Harmattan winds. Further description of the sampling process is described in Laskaris et al [47].…”
Section: Measures Of Real-time Personal Pm 25 Levelsmentioning
confidence: 99%
“…However, in future studies, the use of repeated measurements of micronutrient biomarkers will be required to better characterise the micronutrient status of the recyclers and their effects on health outcomes. Further, we asked questions about job activities and present a simple interpretation here (3 general categories) though other studies have shown that e-waste recyclers tend to perform many tasks onsite (Laskaris et al, 2019). We tried to put the ndings into context by comparing values with "background populations" but there is a lack of understanding of such values from Africa, especially from vulnerable recycler populations based in low-and middleincome countries.…”
Section: Limitations and Strengthsmentioning
confidence: 99%